Effect of Sr2+ and Ba2+ doping on structural stability and mechanical properties of La2NiO4+δ - Akbari-Fakhrabadi, Ali (2020)
Structural and mechanical Characterizations of La1.8M0.2NiO4+δ (M: Sr and Ba) prepared by low frequency ultra-sound assisted synthesis technique and sintered at different temperatures were studied. HRTEM and XRD analyses showed the uniform shape of calcined nanocrystalline powders with the particle size of less than 100 nm with mixed phases, which were refined by Rietveld method using orthorhombic (Fmmm) and tetragonal (F4/mmm) structures. Sintering La1.8Sr0.2NiO4+δ and La1.8Ba0.2NiO4+δ compacted discs at temperatures higher than 1300 °C and 1250 °C, respectively, resulted in appearance of extra peaks close to a monoclinic phase. Doping La2NiO4+δ with Sr2+ and Ba2+ did not affect its sinterability and average grain size significantly, however, Ba2+ improved the elastic modulus and microhardness, while Sr2+ improved the fracture toughness.